The Battle for God : Fundamentalism in Judaism, Christianity and Isla - Armstrong, Karen (New York Harper Perennial, 2000)
"In The Battle for God, Karen Armstrong shows us how and why fundamentalist groups came into existence and what they yearn to accomplish." "We see the West in the sixteenth century beginning to create an entirely new kind of civilization, which brought in its wake change in every aspect of life - often painful and violent, even if liberating. Armstrong argues that one of the things that changed most was religion.
Include Bibliography, Note and Index
Keywords: Religious fundamentalism -- Islamic fundamentalism -- Orthodox Judaism -- Fundamentalism